2016
DOI: 10.1186/s12909-016-0814-y
|View full text |Cite
|
Sign up to set email alerts
|

Global health education in Germany: an analysis of current capacity, needs and barriers

Abstract: BackgroundIn times of increasing global challenges to health, it is crucial to create a workforce capable of tackling these complex issues. Even though a lack of GHE in Germany is perceived by multiple stakeholders, no systematic analysis of the current landscape exists. The aim of this study is to provide an analysis of the global health education (GHE) capacity in Germany as well as to identify gaps, barriers and future strategies.MethodsAn online search in combination with information provided by student re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 27 publications
(35 reference statements)
0
32
1
Order By: Relevance
“…A recent study by Kaffes et al identified 13 medical faculties offering global health education in Germany, a lower number than was identified by our analysis [39]. This discrepancy likely results from the narrower inclusion criteria of Kaffes et al, who only included courses with 'global health' or the German translation "globale Gesundheit" in their title, compared to our use of the Consortium of Universities for Global Health definition of global health.…”
Section: Plos Onecontrasting
confidence: 63%
“…A recent study by Kaffes et al identified 13 medical faculties offering global health education in Germany, a lower number than was identified by our analysis [39]. This discrepancy likely results from the narrower inclusion criteria of Kaffes et al, who only included courses with 'global health' or the German translation "globale Gesundheit" in their title, compared to our use of the Consortium of Universities for Global Health definition of global health.…”
Section: Plos Onecontrasting
confidence: 63%
“…Reconciliation and integration of old public health service tasks (eg, infectious disease control, and environmental and hospital hygiene) with new public health methods and ideas (eg, systemic disease prevention and health promotion, a focus on the wider determinants of [global] health, and advanced data management, analysis competencies and infrastructures) is overdue. 3 The fostering of a strong domestic public health sector is highly relevant to Germany's expanding role in global health: as a knowledge base, for capacity building, and to provide leadership. The Future Forum Public…”
Section: Germany's Expanding Role In Global Healthmentioning
confidence: 99%
“…In an analysis of education and training on global health issues in German universities, Kaffes and colleagues 63 paint a rather sober picture of future professionals and the knowledge and skills they are being equipped with to address global health issues, particularly when it comes to broader, inter disciplinary education and training, with "only onethird of medical schools and less than a third of all healthrelated degree programs in Germany offering some kind of education in Global Health". 63 Thus, although Germany has been tremendously eager to become more visible across core institutions of global health governance, the low prioritisation of global health in its universities' curricula reflects a gap that needs to be filled as Germany aims to adequately staff its contribution to global health. Compared with North America and the UK, Germany is simply outstripped in its global health education activities, both in the number and degree options as well as in research on global health education.…”
Section: Aiming For Policy Coherence and Stakeholder Involvement In Gmentioning
confidence: 99%
“…Compared with North America and the UK, Germany is simply outstripped in its global health education activities, both in the number and degree options as well as in research on global health education. 63 The Ministry of Education and Research has created some incentives for German universities and researchers to become more interdisciplinary in their research of global health issues (eg, in neglected tropical diseases), 64 but there needs to be a strongerr emphasis on global health education and training at the level of federal ministries, state ministries, and individual universities. This gap is also an indication of weak professional and scientific organisations whose lobby power is not forceful enough.…”
Section: Aiming For Policy Coherence and Stakeholder Involvement In Gmentioning
confidence: 99%